Osteopathology and insect traces in the Australopithecus africanus skeleton StW 431 - Zipfel, B.; Jakata, K.; Bonney, H.; Odes, E.J.; Parkinson, A.H.; Randolph-Quinney, P.S.; Berger, L.R. (Academy of Science of South Africa (ASSAf), 2017)
We present the first application of high-resolution micro computed tomography in an analysis of both the internal and external morphology of the lumbar region of StW 431 - a hominin skeleton recovered from Member 4 infill of the Sterkfontein Caves (South Africa) in 1987. The lumbar vertebrae of the individual present a number of proliferative and erosive bony processes, which were investigated in this study. Investigations suggest a complex history of taphonomic alteration to pre-existing spinal degenerative joint disease (SDJD) as well as post-mortem modification by an unknown insect. This study is in agreement with previous pathological diagnoses of SDJD which affected StW 431 and is the first time insect traces on this hominin are described. The results of this analysis attest to the complex series of post-mortem processes affecting the Sterkfontein site and its fossil assemblages.
Keywords: Micro computed tomography; Palaeopathology; Spinal degenerative joint disease; Sterkfontein; Taphonomy; Bone; Disease incidence; Fossil assemblage; Hominid; Insect; Morphology; Osteology; Paleoecology; Pathology; Skeleton; Tomography; Trace fossil; Gauteng; South Africa; Australopithecus africanus; Hexapoda